Charismatic Leadership in Improving The Quality of Resources in Islamic Boarding School - Hariadi, Nur; Sumardjoko, Bambang; Maryadi (Kharisma: Jurnal Administrasi dan Manajemen Pendidikan, 2024)
This article highlights the critical role of leadership in shaping the quality of education and human resources within Islamic boarding schools, which face challenges in adapting to modern management standards and ensuring sustainable development. This research addresses the low quality and loyalty of human resources and the management system in Islamic boarding schools, particularly through the charismatic leadership of caregivers at Muhammadiyah Darul Arqom Karanganyar Islamic Boarding School. This article gathers primary data from in-depth interviews with Islamic boarding school managers, students, and alums and secondary data from relevant literature. Data collection techniques include observation, interviews, and documentation studies.The findings reveal that caregivers must integrate various leadership styles, with charismatic abilities as a distinctive identity that significantly influences human resource elements. Motivation for subordinates, educators, and students should be carried out effectively through person-to-person, group-to-group, and collaborative approaches. The study concludes that improving the quality of education at Pesantren Muhammadiyah Darul Arqom Karanganyar involves transformational leadership patterns focused on enhancing human resource capabilities by encouraging mindset shifts, motivating, and providing development opportunities through training, workshops, and seminars. Future research should explore the impact of digital tools and technology on leadership effectiveness in Islamic boarding schools and examine strategies for fostering global competitiveness among human resources in similar educational institutions.